2005
DOI: 10.1242/dev.01541
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of trigeminal axon navigation and patterning with tooth organ formation: epithelial-mesenchymal interactions, and epithelial Wnt4 and Tgfβ1 regulate semaphorin 3a expression in the dental mesenchyme

Abstract: During development, trigeminal nerve fibers navigate and establish their axonal projections to the developing tooth in a highly spatiotemporally controlled manner. By analyzing Sema3a and its receptor Npn1 knockout mouse embryos, we found that Sema3a regulates dental trigeminal axon navigation and patterning, as well as the timing of the first mandibular molar innervation,and that the effects of Sema3a appear to be mediated by Npn1 present in the axons. By performing tissue recombinant experiments and analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(150 citation statements)
references
References 64 publications
5
134
0
9
Order By: Relevance
“…5 Histologically, the pioneer dental axons have been shown to emerge from the deep mandibular inferior alveolar nerve, where they grow toward the first molar tooth germ at embryonic (E) day 12.5. [21][22][23][24] Approximately half a day later, the first dental axons reach the target area of the bud-stage tooth germ. During the tooth-specific morphogenetic cap and bell stages, nerves innervate the tooth germ, to surround Figure 1.…”
Section: The Adult Tooth Nerve Supply and Its Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Histologically, the pioneer dental axons have been shown to emerge from the deep mandibular inferior alveolar nerve, where they grow toward the first molar tooth germ at embryonic (E) day 12.5. [21][22][23][24] Approximately half a day later, the first dental axons reach the target area of the bud-stage tooth germ. During the tooth-specific morphogenetic cap and bell stages, nerves innervate the tooth germ, to surround Figure 1.…”
Section: The Adult Tooth Nerve Supply and Its Functionsmentioning
confidence: 99%
“…32,23,13,25,26 the mesenchymal dental follicle target area, which ultimately forms the periodontium (during root formation and tooth eruption) that attaches roots to alveolar bone. 10,13,23,25,26 Of note, although the nerves already surround the developing tooth organ during embryonic stages, axons will only grow into the mesenchymal dental pulp post-natally. Typically this occurs after a delay of about 10 days (from the first encounter of axons with the tooth target), on postnatal day 3-4.…”
Section: The Adult Tooth Nerve Supply and Its Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules generally attract the growth cones. Nerve ingrowth towards the dental epithelium and the dental papilla is actively inhibited and regulated by semaphorins, and by semaphorin3a in particular [58]. Semaphorin3a is expressed in the dental follicle and directs the growth of trigeminal axons along precise paths [58].…”
Section: Innervation and Teethmentioning
confidence: 99%
“…The innervation of the tooth is initiated relatively late during development and involves sensory and sympathetic nerves. Complex molecular mechanisms regulate the timing and pattern of tooth innervation (Fried et al, 2007;Kettunen et al, 2005;Luukko et al, 2008). It has been suggested that the epithelium instructs and controls dental axons navigation in the dental mesenchyme (Luukko et al, 2008).…”
Section: Innervationmentioning
confidence: 99%